Angina pectoris, ECG findings and blood pressure of foundry workers in relation to carbon monoxide exposure. - Hernberg, Sven; Kärävä, Risto; Koskela, Riitta-Sisko; Luoma, Katariina (Scandinavian Journal of Work, Environment & Health, 1976)
A prevalence study on angina pectoris, ECG changes, and blood pressure was carried out with those 1,000 workers (response rate 93.1%) with the longest exposure time (minimum 4.2 years) from a statistical sample of 20 foundries. The history of angina was obtained from a questionnaire recommended by the World Health Organization, and the ECGs were coded according to the Minnesota code. On the basis of measurements of the concentration of carbon monoxide (CO) in the air, the workers were divided into three occupational exposure groups, one with definite CO exposure, one with slight or occasional CO exposure, and one without CO exposure. Allowance was also made for present and past smoking habits. All comparisons were made on an intrastudy basis between the different subcategories. The prevalence of angina showed a clear dose-response relationship with regard to CO exposure from either occupation, smoking, or both, but no such trend was found for ECG findings suggestive of CHD. These results may suggest a greater sensitivity in detecting CHD on the part of the angina questionnaire. The systolic and diastolic blood pressures of CO exposed workers were slightly higher than those of other workers when age and smoking habits were taken into consideration. However, exposure to heat was intermixed with exposure to CO. It could be shown that selection based on health had operated in the foundries. Hence, the prevalence found can be considered to be underestimates of the "true" occurrence of cardiac disorders. Nevertheless both angina and "coronary" ECG findings were more prevalent than in other methodologically comparable studies on the general population or industrial workers without toxic exposure.
Keywords: angina pectoris; blood pressure; carbon monoxide exposure; ECG finding; foundry work; foundry worker; prevalence study